A first confirmed record of the Indian Crested Porcupine Hystrix indica (Mammalia: Rodentia: Hystricidae) in the United Arab Emirates - Maral K. Chreiki (Journal of Threatened Taxa, 2018)
We report the first records of the Indian Crested Porcupine (Hystrix indica; Kerr, 1792) in the United Arab Emirates (UAE), approximately 600km beyond its known range in Arabia.  Images of H. indica were taken by camera traps at two locations in Wadi Wurayah National Park (WWNP), Fujairah, in three separate events in 2015 and 2016.  Long-term occupancy of porcupines was confirmed via social surveys conducted in four villages bordering WWNP.  These findings represent a previously unrecorded and most likely isolated subpopulation of H. indica.  Further study is warranted to assess the genetic and demographic resilience of the population.